Considering the Sources: Comparing Linking Patterns in Usenet and Blogs - McGlohon, Mary; Hurst, Matthew (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Usenet is a decentralized discussion community predating blogs by decades. Just as there are a wide range of political blogs, many Usenet sub-communities focus on politics. However, we find these two communities are very different in terms of source content. In this work we compare linking patterns of the political Usenet with a well-known political blog and news aggregator, Memeorandum, with respect to coverage of news and blog sources, attention of stories, and timeliness of links.